A Better Approach to After-Action Reviews - Fletcher, Angus; Cline, Preston B.; Hoffman, Matthew (Harvard Business Review, 2023)
In the decades since the Army created the After Action Review (AAR), b usinesses have embraced the practice as a way of learning from both fa ilure and success. But all too often the practice gets reduced to noth ing more than a pro forma exercise. The authors of this article descri be the history and philosophy of the original AAR, debunk three myths about the practice that impede its proper use, and finally suggest thr ee improvements that can help business leaders make the most of it.
Keywords: Collaboration and teams; Crisis management; Project management